2018
DOI: 10.1186/s12885-018-4423-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotional predictors of bowel screening: the avoidance-promoting role of fear, embarrassment, and disgust

Abstract: BackgroundDespite considerable efforts to address practical barriers, colorectal cancer screening numbers are often low. People do not always act rationally, and investigating emotions may offer insight into the avoidance of screening. The current work assessed whether fear, embarrassment, and disgust predicted colorectal cancer screening avoidance.MethodsA community sample (N = 306) aged 45+ completed a questionnaire assessing colorectal cancer screening history and the extent that perceptions of cancer risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…A study limitation is that the EBBS is not a published scale (Reynolds et al., ). However, in the present study, although it was not a reliable tool for identifying discrete emotions, the EBBS did detect faecal disgust‐based emotional reactions to bowel screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study limitation is that the EBBS is not a published scale (Reynolds et al., ). However, in the present study, although it was not a reliable tool for identifying discrete emotions, the EBBS did detect faecal disgust‐based emotional reactions to bowel screening.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional barriers to bowel screening (EBBS) were administered to assess emotional responses to bowel screening (Reynolds, Bissett, Reid, & Consedine, ). The scale adopts a 5‐point agreement scale (1 = strongly disagree , and 5 = strongly agree ), across 20 items.…”
Section: Methodsmentioning
confidence: 99%
“…Medical procedures that are intimate, such as colonoscopies and pelvic/prostate examinations, can cause discomfort and embarrassment for patients. Previous studies have reported that the embarrassment experienced during these situations can prevent patients from engaging in medical examinations (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…colonoscopy insertion, surgical incision and wound appearance), hygiene (e.g. unpleasant odour) and death (Haidt, McCauley, & Rozin, 1994; Reynolds, Bissett, & Consedine, 2018; Reynolds, Consedine, & McCambridge, 2014). Given its evolutionary grounding as a vital element of the “behavioural immune system” (Schaller & Park, 2011), disgust is particularly relevant in facilitating psychological reactions to disease and its treatment (Reynolds, Consedine, Pizarro, & Bissett, 2013).…”
Section: Introductionmentioning
confidence: 99%